CHNQD-00603 Promotes Osteogenic Differentiation of Bone Marrow Mesenchymal Stem Cells by the miR-452-3p-Mediated Autophagy Pathway - Xin, Shanshan; Li, Shao-Ming; Gao, Ling; Zheng, Jing-Jing; Wu, Yan-Wei; Shao, Chang-Lun; Ren, Wen-Hao; Zhi, Keqian (Frontiers in Cell and Developmental Biology, 2021)
Background: Periodontitis is a chronic and progressive disease，accompanied by bone loss. It is still a challenge to restore the bone structure. The osteogenic differentiation of bone marrow mesenchymal stem cells（BMSCs) plays a decisive role in the bone restoration and regeneration. Marine natural products (MNPs) have been proven to have multiple biological activities, including anti-tumor, anti-inflammation. However, the exploration of MNPs in osteogenesis is far from enough. Methods: we obtained a series of derivatives through structural optimization from 4-phenyl-3,4-dihydroquinolin-2(1H)-one alkaloids isolated from Scopulariopsis sp. Some preliminary cytological experiment identified that CHNQD-00603 may promote the osteogenic differentiation of BMSCs. The osteogenic differentiation was further evaluated by qRT-PCR, ALP staining and Alizarin red S staining. The level of autophagy was assessed and validated by WB, qRT-PCR and Transmission electron microscope. According to the expression of autophagy-related genes, we predicted and examinated the potential miRNAs by bioinformatics. Results: qRT-PCR, ALP staining and activity assay and Alizarin red S staining showed that CHNQD-00603 at 1ug/ml was the best concentration to promote osteogenic differentiation. Further investigation indicated that CHNQD-00603 activated autophagy, and the inhibition of autophagy by 3-MA attenuated CHNQD-00603-enhanced osteogenic differentiation. Subsequently, the results from bioinformatics and qRT-PCR indicated that miR-452-3p may be a regulator of autophagy and osteogenesis. Furthermore, we transfected BMSCs with miR-452-3p NC and mimics separately to further determine the function of miR-452-3p. The data showed that overexpression of miR-452-3p moderated the level of autophagy and the osteogenic differentiation of CHNQD-00603-treated BMSCs. Conclusion: Our data suggested that CHNQD-00603 promoted osteogenic differentiation of BMSCs by elevating the level of autophagy. Meanwhile, miR-452-3p played a regulatory role in this process.